Climate change in the Andes: predictions, perceptions and adaptation by peruvian rice farmers - Useche, Pilar; Anglade, Boaz; Muriel, Juliana; Twyman, Jennifer (International Center for Tropical Agriculture, 2020)
Rice cultivation in Peru exemplifies the complex nature of the interaction between changing climatic conditions and households’ decisions on how to cope with these changes given their constraints and perceptions. In this study, we look at this interaction, focusing on small-scale household farmers that depend on rice production for their livelihoods. We first examine men’s and women’s perceptions of climatic changes and compare them to aggregate and weather station observations of changes in climatic indicators. Second, we examine the various adaptation practices used by rice farmers to cope with climate change, and what determines these practices using a multivariate probit analysis.